ANALISIS FRAMING BERITA “PERBEDAAN PENDAPAT SEPUTAR PERMENDIKBUD KEKERASAN SEKSUAL” MEDIA KOMPAS DAN VICE - Dzakhirotul Mufidah (Universitas Singaperbangsa Karawang, 2022)
This research is focused on two news articles that discuss the Differences in Opinion of the Minister of Education and Culture on Sexual Violence. Researchers analyzed two media covering the news, namely Kompas TV Media and Vice. The method used in this study is to analyze the content and the approach used is qualitative by describing the results of the analysis. Researchers used the Framing Analysis Theory of Zhong Dang Pan and Gerald M. Kosicki. This theory discusses 4 structures, namely syntax (news chart), thematic (point of view on an event), script (packing news in 5W1H), and theoretical (emphasizing a meaning from the description of word choice or style). The results found are that these two news stories use the same media, namely the opinions of the sources are divided into two groups, namely the pro and contra. Based on the results of analytical research, it was found that Media Vice included more sources than Media Kompas TV. Media Vice also quotes more from Media Kompas TV. The number of quotes from the pros and cons also has a significant comparison. Keywords: Framing Analysis Zong Dan Pan and Gerald M. Kosicki, Kompas TV, Vice